Implementasi Pengelolaan Data Sektoral Pada Portal Satu Data Sumsel di Dinas Sosial Provinsi Sumatera Selatan - Dhea Ananda; Gusmelia Testiana (GLOBAL SCIENTS PUBLISHER, 2026)
The implementation of the One Data Indonesia policy encourages every government institution to manage data accurately, integratively, and sustainably to support data-driven governance and improve the quality of public services. The Social Service of South Sumatra Province, as one of the Regional Government Organizations, plays an important role in providing and managing sectoral data through the South Sumatra One Data Portal. This study aims to analyze the implementation of sectoral data management on the South Sumatra One Data Portal at the Social Service of South Sumatra Province. The research employed a descriptive method with a qualitative approach using observation, interviews, and documentation techniques during the internship program. The results indicate that sectoral data management is carried out through data collection, verification, processing, input, and publication stages. Several obstacles were identified, including incomplete data, differences in data formats among divisions, and delays in data submission. Improvement efforts were made through enhanced coordination among divisions, data format standardization, and periodic verification, thereby supporting the availability of quality, integrated, and accountable data as a basis for planning, evaluation, and decision-making processes within the South Sumatra Provincial Government.